(untitled) (Indus Journal of Bioscience Research, 2025)
Background: Advanced Nurse Practitioners (ANPs) are a vital part of the emergency healthcare services worldwide, but their role in Pakistan remains unexplored. Understanding the awareness and attitudes of healthcare professionals toward ANPs is crucial for their successful integration into the emergency healthcare services. Objective: This study aimed to assess the awareness and attitudes of doctors, nurses, and healthcare administrators regarding the role of ANPs in emergency healthcare setting. Methodology: A cross-sectional study was conducted in the Emergency Department of Holy Family Hospital, Rawalpindi, from January to April 2024. Total 184 participants (73 nurses, 102 doctors, 9 healthcare administrators) were included using convenience sampling. Data were collected through adaptation and modified 32-item "Attitudes towards ANPs Questionnaire (AANPQ)" and analyzed using SPSS 29.0. Ethical standards, including informed consent and confidentiality, were strictly observed. Results: The study showed that 92.9% of participants had a clear understanding of the ANP role in emergency healthcare, with strong agreement on ANPs’ involvement in patient assessment (92.9%), investigations (89.7%), treatment (89.2%), and discharge (79.9%). Attitudes were generally highly positive, with 88% viewing ANPs as an advancement in nursing, and 91.3% acknowledging their role in educating colleagues. Conclusion: This study showed moderate to high positive awareness and moderate to high positive attitudes toward the role of ANPs in emergency healthcare at Holy Family Hospital. Clearer role definitions and professional recognition are needed for full integration. Organizational efforts should focus on education, role clarification, and policy development, while individuals should prioritize continuous professional development and collaboration to improve emergency healthcare in Pakistan.